PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KORAN KALTIM POST DI KOTA SAMARINDA - -, Muhammad Rizali (EKONOMIA, 2019)
The purpose of this study was to determine the effect of products, prices, promotions, and distribution on purchasing decisions of Kaltim Post newspapers both partially and simultaneously. Broadly speaking the problem is formulated as follows, whether there is influence of product, price, promotion, distribution on purchasing decisions in the Kaltim Post newspaper.The theoretical basis of this research is marketing management that focuses on the marketing mix. The hypothesis proposed is that there are positive and significant influences on products, prices, promotions, distribution on purchasing decisions of the Kaltim Post newspaperThe analytical tool used is multiple linear regression with t test and F test. Primary data obtained from 30 people of Kaltim Post customers in Samarinda City were taken by Purposive sampling technique.The results showed that the purchasing decision of the Kaltim newspaper on product, price, promotion, and distribution was very high, which meant that the contribution of all variable effects on purchasing decisions, while others were influenced by factors other than product, price, promotion, and distribution. The results of the t test show that all marketing mix variables partially have a positive and significant effect on the purchasing decisions of the Kaltim Post newspaper. This means that the better the consumer's perception of the product, price, promotion and distribution, the higher the level of consumer decision to buy the Kaltim Post newspaper. The results of the F test analysis show that all marketing mix variables simultaneously have a significant effect on purchasing decisions of the Kaltim Post newspaper.